Hypercalcemia and parathyroid hormone-related peptide expression in a 3 months old boy with Colon Hemangioendothelioma - Kelly, Maury (2019)
Epithelioid hemangioendothelioma (HEE) is a tumor of vascular origin, infrequent in the pediatric age and even more infrequent at intestinal level. To our knowledge, there are no previous reports of pediatric patients with malignant humoral hypercalcemia associated with this tumor. Humoral mechanism is seen more often in lung, uterine cérvix, skin and esophagus tumors. The presence of hypercalcemia appears to be an ominous prognostic sign.Objective: To report the first case of a patient with hypercalcemia related to PTH-rP associated with Colon HEE in a pediatric patient.Case description: A 3 months years old boy was admited because of clinical worsening and palpable abdominal mass. Initial laboratory investigation revealed hypercalcemia with the following workup: PTH: 1.65 pg/ml, calcium: 25.1 mg/dl, phosphorus 2.9 mg/dl 25ohvitamine D: 25.2 ng/ml, Urine catecholamines were normal. Ultrasound visualized a highly vascularized tumor with calcifications in retroperitoneum of 8×6×6 cm located between liver and right kidney. Biphosphonates and Calcitonin were iniciated without improvement. Biopsy reported epithelioid hemangioendothelioma and angiography revealed tumor irrigated by the middle colic artery. Selective embolization was performed with spongostan and 24 hours later, tumor exeresis was achieved. PTHrP mRNA was identified in the tumor. After surgery the patient attained normocalcemic state, PTH levels normalized and remained normocalcemic to date, 18 months later.Conclusion: We report the first case of PTH-rp related hypercalcemia, with mesocolon epithelioid hemangioendothelioma a pediatric patient. PTH-rp mRNA was detected at tumor level, and the patient resolved hypercalcemia with tumor resection, remaining normocalcemic and with normal PTH levels since then. Selective embolization was important in order to facilitate tumor resection successfully, and improving morbidity and mortality of this surgery.Disclosure: The authors declared no competing interests.